Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Re: An operation @ is defined by the equation a@b = (a - b) / (a [#permalink]

Show Tags

24 Nov 2013, 11:04

Bunuel wrote:

Walkabout wrote:

An operation @ is defined by the equation a@b = (a - b) / (a + b), for all numbers a and b such that a ≠ -b. If a ≠ -c and a@c = 0, then c =

(A) -a (B) -1/a (C) 0 (D) 1/a (E) a

Given that \(a@b = \frac{a - b}{a + b}\), thus \(a@c = \frac{a - c}{a + c}\).

Also given that \(a@c = \frac{a - c}{a + c}=0\) --> \(a-c=0\) --> \(a=c\).

Answer: E.

Hi Bunnuel,

I've never senn such a task before in my life. Could you please explain what the @ means or what the whole expression "operation @" means? or do you recommend any books/links for this ? (I already worked through MGMAT Foundations of Math but really NEVER seen this before)

An operation @ is defined by the equation a@b = (a - b) / (a + b), for all numbers a and b such that a ≠ -b. If a ≠ -c and a@c = 0, then c =

(A) -a (B) -1/a (C) 0 (D) 1/a (E) a

Given that \(a@b = \frac{a - b}{a + b}\), thus \(a@c = \frac{a - c}{a + c}\).

Also given that \(a@c = \frac{a - c}{a + c}=0\) --> \(a-c=0\) --> \(a=c\).

Answer: E.

Hi Bunnuel,

I've never senn such a task before in my life. Could you please explain what the @ means or what the whole expression "operation @" means? or do you recommend any books/links for this ? (I already worked through MGMAT Foundations of Math but really NEVER seen this before)

@ is a made up operation (function), defined by the equation a@b = (a - b)/(a + b). For example 2@3=(2-3)/(2+3)=-1/5.

An operation θ is defined by the equation... [#permalink]

Show Tags

08 Apr 2014, 19:35

Hello and thank you for your help! I don't understand the answer provided by my book.

Question: An operation θ is defined by the equation a θ b = a-b/a+b, for all numbers a and b such that a does not equal -b. If a does not equal -c and a θ c = 0, then c = ?

Hello and thank you for your help! I don't understand the answer provided by my book.

Question: An operation θ is defined by the equation a θ b = a-b/a+b, for all numbers a and b such that a does not equal -b. If a does not equal -c and a θ c = 0, then c = ?

Answer: Substitute c for b and 0 for a θ c in the given equation and solve for c.

So 0 = a - c / a + c

Multiply each side by a + c

So 0 = a - c So c = a

My question is: why can they substitute c for b?

Source: 12th edition Gmat Review

θ has been defined as an operator which takes input values of two variables and gives the answer by calculating (First variable - Second variable)/(First variable + Second variable). Here a and b are just taken as an example.

a θ b = (a - b)/(a + b) x θ y = (x - y)/(x + y) a θ c = (a - c)/(a + c) It doesn't what the two variables are.

Given a θ c = 0 = (a - c)/(a + c) Then a - c = 0 a = c
_________________

Hello and thank you for your help! I don't understand the answer provided by my book.

Question: An operation θ is defined by the equation a θ b = a-b/a+b, for all numbers a and b such that a does not equal -b. If a does not equal -c and a θ c = 0, then c = ?

Re: An operation @ is defined by the equation a@b = (a - b) / (a [#permalink]

Show Tags

11 May 2015, 03:07

Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________

Need great help How can I know that b can be substituted with c in the new equation ? Hope to hear from you Many thanks

The trick here is to recognize 2 things:

1. Unless you can substitute some variable by c in a@b , how are you going to get the desired relation between a and c? 2. The question stem mentions that the relation for a@b is true for "all numbers a and b". Thus you can substitute c for b and get the desired result.
_________________

This question is an example of a 'Symbolism' question; in these types of prompt, the GMAT 'makes up' a math symbol, tells you how to use it, then asks you to use it to perform a calculation.

Here, we're given a made-up calculation that uses the @ symbol.... A@B = (A-B)/(A+B)

eg. 1@2 = (1-2)/(1+2) = -1/3

We're told that A@C = 0 and A ≠ -C. We're asked for the value of C....

We can TEST VALUES to answer this question, but we have to start by TESTing a VALUE for A, then figure out what C would have to equal....

IF.... A = 2 A@C = 2@C = (2-C)/(2+C) = 0

So, what would C have to equal to make this equation equal 0?

(2-C)/(2+C) = 0

Since we're dealing with a fraction, we need the NUMERATOR to equal 0. In this example, that would ONLY happen when C = 2. So we're looking for an answer that equals 2 when A=2.

Answer A: - A = -2 NOT a match Answer B: -1/A = -1/2 NOT a match Answer C: 0 NOT a match Answer D: 1/A = 1/2 NOT a match Answer E: A = 2 This IS a MATCH

An operation is defined by the equation ab = (a - b) / (a [#permalink]

Show Tags

27 Jul 2015, 21:27

Dear All, Many thanks , I'm sorry,i need help to understand it

Can I also know b can be replaced by c based on the following statements: a not equal -b a not equal -c As it indicate a-b and a-c has same relationship , since it is the same relationship,I can substitute b with c. Appreciate your comments Hope to hear from you many thanks for the great help

Last edited by apple08 on 28 Jul 2015, 06:08, edited 1 time in total.

An operation is defined by the equation ab = (a - b) / (a [#permalink]

Show Tags

27 Jul 2015, 21:53

Or since a@c = 0, I can plug c into b since @ is common in both a@b and a@c. How can I make use of "a not equal to -b" or "a not equal to -c"? Is it from "a not equal to -c" I know c is not equal to -a, hence eliminate answer (a) -a , really appreciate your great help, many many thanks

Re: An operation is defined by the equation ab = (a - b) / (a [#permalink]

Show Tags

16 Jun 2016, 04:59

Walkabout wrote:

An operation @ is defined by the equation a@b = (a - b) / (a + b), for all numbers a and b such that a ≠ -b. If a ≠ -c and a@c = 0, then c =

(A) -a (B) -1/a (C) 0 (D) 1/a (E) a

We are given that operation @ is defined by a@b = (a-b)/(a+b).

We are also given that a@c = 0; thus, according to the operation, all instances of a can remain and all instances of b will be replaced with variable c. We then set that entire expression to zero.

(a-c)/(a+c) = 0

We can multiply both sides of the equation by a+c and then solve for a:

a – c = 0

a = c

The answer is E.
_________________

Jeffrey Miller Scott Woodbury-Stewart Founder and CEO

gmatclubot

Re: An operation is defined by the equation ab = (a - b) / (a
[#permalink]
16 Jun 2016, 04:59

Happy New Year everyone! Before I get started on this post, and well, restarted on this blog in general, I wanted to mention something. For the past several months...

It’s quickly approaching two years since I last wrote anything on this blog. A lot has happened since then. When I last posted, I had just gotten back from...

Post-MBA I became very intrigued by how senior leaders navigated their career progression. It was also at this time that I realized I learned nothing about this during my...